Bovine endometrial cells as an in vitro model to address early embryo maternal cross-talk - Slootmans, Jens; Sponchiado, Mariana; Leroy, Jo (Student Undergraduate Research E-journal!, 2019)
We optimized a bovine endometrial epithelial cell (BEEC) line as a valuable research model for the study of early embryo-maternal interactions in vitro. Therefore, we aimed to characterize the BEEC monolayers along the primary culture and the first three passages with respect to the expression of cell-origin markers, by immunofluorescence, and abundance of functional key transcripts, by Real Time PCR. BEECs isolated from uteri (at early luteal phase) ex vivo were cultured and subpassed three times. Based on the markers studied, we conclude that BEEC monolayers undergo an epithelial-mesenchymal transition in vitro but preserve functional characteristics after few passages.